ANALISIS KANDUNGAN LOGAM BERAT TIMBAL (Pb) PADA PRODUK OLAHAN SUSU - Evi Mardiastuty Silalahi; Endang Purwanti (LPPM Universitas Terbuka, 2021)
Lead (Pb) is a toxic substance that easily accumulates in human organs and can cause health problems such as anemia,impaired kidney function and impaired nerve, brain and skin tissue system. Analysis of the heavy metal content of Lead (Pb) in dairy products is needed to determine the feasibility of consuming these products. This research was conducted from June until August 2020 at Laboratory. The objective of this research was to determine lead content in dairy products in the form of pasteurized milk, cheese, butter and yoghurtusing Inductively Couple Plasma-Mass Spectrometry (ICP-MS) method. Samples were prepared usingthe wet destruction method with HNO365% ultrapure H2O230% ultrapure and HCl ultrapure. The contents of lead obtained from the research were, for the first batch: pasteurized milk< 0,001 mg/kg, cheese < 0,001 mg/kg, butter 0,004 mg/kg and yoghurt < 0,001 mg/kg. For the second batch of the pasteurized milk, the lead contents were: pasteurized milk 0,020 mg/kg, cheese 0,011 mg/kg, butter 0,006 mg/kg and yoghurt0,025 mg/kg. The lead contents for third batch were: pasteurized milk < 0,001 mg/kg, cheese 0,008 mg/kg, butter 0,004 mg/kg, yoghurt< 0,001 mg/kg. The results of this study were then compared Maximum Limit of Heavy Metal in Food according to SNI 7387 : 2009 and BPOM Regulation No. 23 year 2017 .